Characteristics of PM1 over Shanghai, relationships with precursors and meteorological variables and impacts on visibility. (July 2018) - Zhou, Guangqiang; Xu, Jianming; Gao, Wei; Gu, Yixuan; Mao, Zhuocheng; Cui, Linli
Abstract: The long-term characteristics of submicron particles (PM1 ) over Shanghai and their contributing factors (including precursor gases and meteorological variables), as well as their impact on visibility, were investigated using in situ measurements from Jan 1st, 2015, to Dec 31st, 2016. A discretization method was introduced to identify the impact of each contributing factor on PM1 . The results show that the annual mean PM1 concentration over Shanghai is ∼28 μgm −3, which accounts for 69% of fine particles (PM2.5 ). The PM1 concentration shows obvious temporal variations on the scales of days, weeks, months, and years. Its diurnal pattern shows higher values in the daytime (with two peaks) than in the nighttime, which is different from the pattern for PM2.5 with high/low values in the nighttime/daytime. During a week, the PM1 concentration is the lowest on Tuesday and the highest on Friday. The discretized approach reveals that PM1 shows good linear relationships with its gaseous precursors and with meteorological variables under most conditions. The concentration of PM1 increases with increases in SO2, NO2, and NO (<34 ppb) with slopes of 3.37, 1.17, and 1.08 μgm −3 per ppb precursor, respectively. This approach and the slopes were confirmed by the comparison of the observed and calculated PM1 changes with the day of the week. PM1 is negatively (positively) correlated with ozone (O3 ) when O3 is <30 (>30) ppb. PM1 are negatively correlated with precipitation intensity, relative humidity (RH, >35%), and wind speed (>1.5 ms -1 ), and their rates of decrease are 3.3, 0.26, and 5.9 μgm −3 per 1 mmh −1, 1%, and 1 ms -1, respectively. Other factors (e.g., temperature and pressure) show nonlinear relationships with PM1 concentration, presumably due to their indirect influence on the transport, formation, or accumulation of PM1 . The PM1 concentration has a distinct impact on visibility, and the PM1 /PM2.5 ratio is a key indicator to represent the impact of particulate matter hygroscopicity on visibility. The PM1 /PM2.5 ratio shows an exponential relationship (i.e., PM1 /PM2.5  = 0.76 [(1-RH)/(1–40%)] 0.11 ) with RH with a determination coefficient of 0.98. This parameter combined with the PM2.5 concentration well describes the impact of particulate matter and its hygroscopicity on visibility. Highlights: The long-term continuous measurements were employed and discretization approach was introduced. PM1 level is relatively high over Shanghai and its diurnal pattern differs from that of PM2.5 . PM1 shows good linear relationships with gaseous precursors and some meteorological variables in most discretized situation. PM1 /PM2.5 ratio represents the effect of aerosol hygroscopicity on visibility.